Młode pokolenie Nowej Huty. Socjologiczna analiza społeczności lokalnej - Dargiewicz, Jacek (Wydawnictwa AGH, 2006)
Author describes phenomenon of local society among young residents of Nowa Huta postindustrial district of Cracow. Researcher portrays it by considering four elements: degree of identification with the society of Nowa Huta, social relationships of people, the knowledge about neighborhood (as well historical as recent), social activity (actions targeted at youth of Nowa Huta and activities of young adult themselves). Author analyses every element of the phenomenon of local society based on partici-pant observation and performance of quality research which includes interviews with young people of the district and experts that deal with the young generation of Nowa Huta. Writer also analysed two newspaper sources, looking for relevant information about the adolescent residents of Nowa Huta.
Young generation of Nowa Huta inhabitants. Sociological study of their local community
Studia Humanistyczne AGH